2013
DOI: 10.1016/j.jcrs.2013.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens prediction accuracy after corneal refractive surgery using K values from 3 devices

Abstract: The Haigis-L using corneal radius with the PCI measurement was the most predictable method for IOL calculation after corneal refractive laser surgery in patients without a clinical history. The TMP 2.0 mm in the scanning-slit topographer and the TNP in the Scheimpflug system may also be relatively predictable keratometric values for IOL calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Unlike previous studies that predominantly calculated IOL formulae using single corneal power (TNP) measured with the Pentacam system, we evaluated various different corneal K readings such as TCRP, TNP, and TRP, and included several zones (3, 4, 5 mm) [242526]. Furthermore, we used the Haigis formula to overcome the limitations of third-generation formulae.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies that predominantly calculated IOL formulae using single corneal power (TNP) measured with the Pentacam system, we evaluated various different corneal K readings such as TCRP, TNP, and TRP, and included several zones (3, 4, 5 mm) [242526]. Furthermore, we used the Haigis formula to overcome the limitations of third-generation formulae.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have shown that without preoperative records, corneal power estimated with the Pentacam HR's TNP calculation can be used for calculating IOL power; however, this approach must be used with caution, as wide limits of agreement have been reported …”
Section: Discussionmentioning
confidence: 99%
“…More advanced techniques that allow one to measure the curvature of both anterior and posterior corneal surfaces, such as optical coherence tomography and other corneal tomography systems including slit-scanning tomography, rotating slit Scheimpflug-camera, and dual- Scheimpflug, are supposed to be methods that best estimate the true corneal power and can be used as an alternative to the CHM. There have been several promising reports of measuring keratometric values using the Orbscan IIz and Pentacam systems to calculate IOL power [ 13 , 20 21 , 27 ]. Although both instruments can directly evaluate the posterior corneal curvature, they use different operating principles.…”
Section: Discussionmentioning
confidence: 99%
“…This could probably lead to underestimation of the IOL power and a consecutive postoperative hyperopia. Recently, other Pentacam values, such as true net power (TNP) and total corneal refractive power (TCRP), showed better performance in assessing postoperative corneal power after corneal refractive surgery in patients without a clinical history [ 21 22 , 27 , 30 31 ]. The TCRP also seemed to accurately reflect the surgically induced refractive change after myopic excimer laser surgery [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation